Bioactivity of Powder and Extracts from Garlic, Allium sativum L. (Alliaceae) and Spring Onion, Allium fistulosum L. (Alliaceae) against Callosobruchus maculatus F. (Coleoptera: Bruchidae) on Cowpea, Vigna unguiculata (L.) Walp (Leguminosae) Seeds - Abiodun A. Denloye (Psyche: A Journal of Entomology)
Laboratory bioassays were conducted to investigate the bioactivity of powders, extracts, and essential oils from Allium sativum L. (Alliaceae) and A. fistulosum L. (Liliaceae) against adults, eggs, and larvae of Callosobruchus maculatus F. (Coleoptera: Bruchidae). On the basis of 48 hr median lethal toxicity (LC50), test plant powders and extracts from A. sativum were more toxic to C. maculatus adults than those from A. fistulosum. The 48 hr LC50 values for the powder against the test insect species were 9.66 g/kg and 26.29 g/kg for A. sativum and A. fistulosum, respectively. Also the 48 hr LC50 values obtained show that aqueous extracts of the test plant species, 0.11 g/L (A. sativum) and 0.411 g/L (A. fistulosum) were more toxic to C. maculatus than the corresponding ethanol extracts. There was no significant difference in the toxicity of vapours from the two test plant species against C. maculatus, although A. sativum gave lower values. The study shows that A. sativum and A. fistulosum have potentials for protecting stored cowpea from damage by C. maculatus.